An Unambiguous Phase-Based Algorithm for Single-Digit Micron Accuracy Distance Measurements using FMCW Radar - Piotrowsky, Lukas; Jaeschke, Timo; Kuppers, Simon; Pohl, Nils (2019 IEEE MTT-S International Microwave Symposium (IMS), 2019)
In this paper an algorithm for accurate distance estimation using a frequency modulated continuous wave (FMCW) radar is presented. First, a phase calibration of the radio and intermediate frequency path transfer function compensates for distance dependent effects. The unambiguous frequency of the target is used for range cell estimation and the ambiguous but highly accurate and precise target phase is combined with this range cell information.To demonstrate the capabilities of the proposed signal processing chain, distance measurements using an 80 GHz wideband FMCW radar sensor with a movable target and a maximum measurement range of up to 5 m have been carried out. The target is mounted on a precision linear track and the position is laser interferometer referenced. For free space measurements with a target in about 1.2 to 5 m distance, the unambiguous single measurement accuracy has been improved from about ±400 μm to ±8 μm. A potential application of a radar system using this algorithm is the online measurement of machine tools.